Tourism and its impact on Dubai’s economy and environment - Rana, Usman Khalid (2012)
ABSTRACT This thesis is an in-depth study of the main money making industry in Dubai, which is Tourism. The boost in economy in Dubai was mainly from that of the tourism industry. In this thesis I will show how Dubai, due to several factors, became one of the main attractions in the Middle East and through out the Gulf Region. I will also provide statistic and figures that will show that increase of Tourism and interest in Dubai as being the “Place to be” for almost the past decade, and why so many people and companies are investing in the county hence leading to the Rise of tourism in Dubai. My research was based mainly on interview I conducted with several expatriates that have been living in Dubai for a long time and some Local people that witnessed the amazing increase of business and tourism in thecountry. My other research was from some Government documents, which gave me statistic from the past years of how Dubai became one of the world’s favorite places for holiday’s makers and what the government did to achieve such an increase in tourism.